In acute promyelocytic leukemia (APL) low BAALC gene expression identifies a patient group with favorable overall survival and improved relapse free survival - Nolte, Florian; Hecht, Anna; Reinwald, Mark; Nowak, Daniel; Nowak, Verena; Hanfstein, Benjamin; Hofmann, Wolf-Karsten; Lengfelder, Eva (Leukemia research, 2013)
We evaluated the prognostic value of BAALC expression in 86 patients with acute promyelocytic leukemia (APL). At 10 years, the overall survival (OS) was 66% in all patients and 75% in patients who achieved a complete remission (CR). Patients in the BAALClow group showed an OS of 87% as compared to 60% in the BAALChigh group (p=0.019). This difference was more pronounced in treatment responders (92% vs. 70%; p=0.035). In multivariate analyses low BAALC expression retained its prognostic relevance. In conclusion, BAALC expression analysis might be useful in further risk stratification in APL patients.
Available online 31 December 2012
Gesehen am 31.10.2018